A tricobalt tetroxide and a preparation method thereof
Patent Information
- Application Number
- CN202510859138.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2026-09-29
- Estimated Expiration
- 2045-06-25
AI Technical Summary
现有的工艺制备得到的四氧化三钴的振实密度较低,导致制得的电极的孔隙率较大,影响电极的压实密度和体积能量密度
[0026](1)本发明在碳酸钴合成期间通过控制制备过程工艺参数,得到的碳酸钴(104)(012)(116)三强峰对应的晶面的平均晶粒尺寸在内,使其具有较高的表面能,促进烧结期间的致密化,从而有利于提高最终制得的成品四氧化三钴颗粒的振实密度。
Smart Images

Figure CN120736568B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode material technology, and specifically relates to a cobalt tetroxide and its preparation method. Background Technology
[0002] Lithium-ion batteries, as high-performance energy storage devices, are widely used in consumer electronics, electric vehicles, and other fields. Among them, the cathode material is a key component determining the battery's energy density, cycle life, and safety. Lithium cobalt oxide, due to its high voltage platform and stable cycle performance, has become one of the mainstream cathode materials for high-end lithium-ion batteries. Cobalt tetroxide, as a precursor of lithium cobalt oxide, directly affects the performance of the final cathode material due to its physical and chemical properties. In industrial production, cobalt tetroxide is mainly produced by wet synthesis of cobalt carbonate precursor, followed by pyrometallurgical calcination. Existing processes yield cobalt tetroxide with low tap density, resulting in higher porosity in the prepared electrode, which affects the electrode's compaction density and volumetric energy density. Summary of the Invention
[0003] This invention aims to at least solve one of the technical problems existing in related technologies. To this end, this invention proposes a cobalt tetroxide and its preparation method, wherein the cobalt tetroxide has excellent tap density.
[0004] The above-mentioned technical objective of the present invention is achieved through the following technical solution:
[0005] A method for preparing cobalt tetroxide includes the following steps:
[0006] (1) A cobalt salt solution is mixed with a precipitant solution containing carbonate ions to obtain a cobalt carbonate slurry. The average grain size of the top three strongest peaks of cobalt carbonate in the cobalt carbonate slurry (104), (012), and (116) is [missing information].
[0007] (2) After the cobalt carbonate slurry is separated into solid and liquid phases, the solid phase is sintered and then depolymerized to obtain the final product.
[0008] In one embodiment, in step (1), the grain size is calculated based on the full width at half maximum (FWHM) of the diffraction peaks of the (104), (012), and (116) crystal planes in the X-ray diffraction pattern of cobalt carbonate. Specifically, it is calculated using the Scherrer formula, which is as follows: Where k is a constant, taken as 0.89; the values of half-width at half maximum (β) and diffraction angle (θ) are obtained by analyzing the XRD pattern. When using this formula to calculate the grain size, the half-width at half maximum (β) of the diffraction peak is converted to radians for calculation. A copper target is used as the X-ray source. Scanning speed: 5° / min.
[0009] In one embodiment, the cobalt ion concentration in the cobalt salt solution is 1.0-2.0 mol / L.
[0010] In one embodiment, the cobalt salt in the cobalt salt solution is at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride.
[0011] In one embodiment, the concentration of carbonate ions in the precipitant is 2.0-3.0 mol / L.
[0012] In one embodiment, the precipitant solution is at least one selected from sodium carbonate solution, potassium carbonate solution, ammonium bicarbonate solution, and sodium bicarbonate solution.
[0013] In one embodiment, the pH of the mixed reaction is 7.5-7.8.
[0014] In one embodiment, the temperature of the mixing reaction is 30-35°C, and the time of the mixing reaction is 30-50 hours.
[0015] In one embodiment, the mixing reaction is carried out with a precipitant solution as the base liquid, and a cobalt salt solution and a precipitant solution are added under stirring.
[0016] In one embodiment, the volume of the base liquid is 1-2 m³. 3 The flow rate of the cobalt salt solution is 500-700 L / h, and the flow rate of the precipitant solution is adjusted according to the pH value of the reaction.
[0017] In one embodiment, the stirring speed is 200-300 r / min.
[0018] In one embodiment, the particle size D50 of the slurry is 4-8 μm.
[0019] In one embodiment, the sintering method is multi-stage sintering with gradually increasing temperature. The initial sintering temperature of the multi-stage sintering is 250-350°C, the final sintering temperature of the multi-stage sintering is 750-800°C, the temperature difference between two adjacent sintering stages is 0-50°C, and the sintering time of each stage in the multi-stage sintering is 2-4 hours.
[0020] In one embodiment, the multi-segment sintering is 10-15 segments.
[0021] In one embodiment, the sintering is carried out in a rotary kiln with high-temperature multi-stage calcination. The rotary kiln is equipped with lifting plates, the height of which is 1%-5% of the inner diameter of the furnace tubes, and the angle between the lifting plates and the tangent of the inner wall of the kiln is 45-55°. The feeding frequency of the rotary kiln is 3-8Hz, and the material layer height accounts for 20%-50% of the height of the lifting plates. There are 12 heating temperature zones with a temperature gradient, and the interval between adjacent temperature zones is 0-50°C. The furnace tube rotation speed is 12-20Hz, and the opening degree of the kiln inlet valve is 75%-100%.
[0022] In one embodiment, the deagglomeration is performed by conveying the material to the powder processing system through a positive pressure conveying system. The positive pressure conveying pressure is 0.10-0.15 MPa, the conveying pump conveys 80-100 kg per batch, and the gas-solid ratio is 30-50 kg / kg.
[0023] In one embodiment, the powder processing system includes a ribbon mixer, a vibrating screen, and an iron remover. The material after pneumatic conveying is mixed, screened, iron removed, and packaged to obtain cobalt tetroxide as a finished product.
[0024] A cobalt tetroxide, prepared by the method described above, wherein the cobalt tetroxide has a particle size D50 of 3.5-6.8 μm and a tap density of 2.6-2.8 g / cm³. 3 .
[0025] The beneficial effects of this invention are:
[0026] (1) In this invention, by controlling the process parameters during the synthesis of cobalt carbonate, the average grain size of the crystal planes corresponding to the three strong peaks of cobalt carbonate (104)(012)(116) is within the range of... The internal structure gives it a high surface energy, which promotes densification during sintering, thus improving the tap density of the final cobalt tetroxide particles.
[0027] (2) In the process of cobalt carbonate synthesis, the present invention obtains cobalt carbonate intermediates with smaller grain size by adjusting the process parameters of low temperature, high pH value and high stirring speed. This results in cobalt carbonate primary particles with fine and tightly packed morphology. The small primary particles have extremely high surface energy and high sintering activity. The atomic diffusion rate is significantly improved during sintering, which is beneficial to obtaining dense cobalt tetroxide particles. However, particle agglomeration is very likely to occur during sintering, which will lead to a decrease in overall tap density. Furthermore, irregular agglomeration will lead to poor particle uniformity. Therefore, during rotary kiln sintering, the height and angle of the lifting plate, the thickness of the material layer and the opening of the air inlet valve are limited to ensure that the material is fully stirred in the furnace tube without sacrificing production capacity. This maintains a high heat exchange efficiency and sufficient gas volume to ensure that the particles are fully oxidized and decomposed, preventing problems such as insufficient particle sintering and particle agglomeration.
[0028] (3) This invention greatly improves the adhesion and agglomeration in the sintering process through meticulous control of the sintering process. Furthermore, a positive pressure conveying system with less dust, smaller footprint, and higher efficiency is used for material transportation. At the same time, the air pressure, conveying volume, and gas-solid ratio of the positive pressure conveying are carefully controlled. By utilizing the airflow shear force and the collision effect between particles, the soft agglomerates of cobalt tetroxide material still present after rotary kiln sintering are fully deagglomerated without particle wear, reducing the probability of particle agglomeration leading to the formation of pores and a decrease in tap density.
[0029] (4) The cobalt tetroxide product obtained by the present invention has high tap density and the production process is simple and controllable. Attached Figure Description
[0030] Figure 1 This is a SEM image of cobalt carbonate obtained during the preparation process in Example 1 of the present invention;
[0031] Figure 2 This is a SEM image of the cobalt tetroxide product prepared in Example 1 of the present invention;
[0032] Figure 3 This is a SEM image of cobalt carbonate obtained during the preparation process of Comparative Example 1 of this invention;
[0033] Figure 4 This is a SEM image of the cobalt tetroxide product prepared in Comparative Example 1 of this invention;
[0034] Figure 5 This is a SEM image of the cobalt tetroxide product prepared in Comparative Example 2 of this invention;
[0035] Figure 6 The image shows a SEM image of the cobalt tetroxide product prepared in Comparative Example 6 of this invention.
[0036] Figure 7 The image shows the XRD pattern of cobalt carbonate obtained during the preparation process in Example 1 of this invention.
[0037] Figure 8 This is a schematic diagram of the internal lifting plate structure of the rotary kiln used in the preparation process of Embodiment 1 of the present invention. Detailed Implementation
[0038] The present invention will be further described below with reference to specific embodiments.
[0039] Example 1:
[0040] A method for preparing cobalt tetroxide includes the following steps:
[0041] (1) Solution preparation: Prepare a cobalt chloride metal solution with a cobalt ion concentration of 2.0 mol / L as a cobalt salt solution, and prepare a sodium carbonate solution with a carbonate ion concentration of 3.0 mol / L as a precipitant solution.
[0042] (2) Cobalt carbonate synthesis: to 10m 3 Add 2m to the reactor 3Sodium carbonate solution was used as the base liquid. The reaction temperature was 35℃, the stirring speed was 200 r / min, the cobalt salt solution flow rate was 500 L / h, and the precipitant solution flow rate was adjusted according to the pH value to control the reaction pH value at 7.5. After the slurry in the reactor was filled, the thickener was turned on for concentration. During the concentration, the cobalt salt solution and precipitant solution were continuously introduced to keep the material level in the reactor constant. After 35 h of reaction, the particle size D50 of the cobalt carbonate slurry was 4.20 μm. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was measured by XRD. SEM image of cobalt carbonate as shown Figure 1 As shown in the figure, the primary particles of cobalt carbonate are fine and uniformly distributed; the XRD pattern of cobalt carbonate is shown in the figure. Figure 7 As shown in Table 1 below, the XRD diffraction peak information of cobalt carbonate is as follows;
[0043] (3) Cobalt carbonate washing: The cobalt carbonate slurry was centrifuged to remove the mother liquor, and washed with pure water 3 times to obtain filter cake;
[0044] (4) Cobalt carbonate sintering: The cobalt carbonate filter cake obtained in step (3) is fed into a rotary kiln for high-temperature calcination. The kiln is equipped with lifting plates, and a schematic diagram of the lifting plates is shown below. Figure 8 As shown, the height of the lifting plate is 5% of the inner diameter of the furnace tube, and the angle between it and the tangent of the kiln inner wall is 55°. Figure 8 In the section a), the rotary kiln feed frequency is 8Hz, the material layer height is 50% of the lifting plate height, there are 12 heating temperature zones with temperature gradient settings, and the calcination temperatures are: 300-350-400-450-500-550-600-650-700-750-750-750, the calcination time for each zone is 2 hours, the furnace tube speed is 20Hz, and the kiln inlet valve opening is 100%.
[0045] (5) Pneumatic conveying: The cobalt tetroxide sintered in the rotary kiln in step (4) is conveyed to the powder processing system through a positive pressure conveying system. The positive pressure conveying pressure is 0.15 MPa, the single conveying weight of the conveying pump is 100 kg, and the gas-solid ratio is 50 kg / kg. After pneumatic conveying, the material is mixed, sieved to remove iron, and packaged to obtain the finished cobalt tetroxide. The SEM image of the finished cobalt tetroxide is shown below. Figure 2 As shown, the particle size D50 of the finished cobalt tetroxide was measured to be 3.72 μm, and the tap density TD was 2.65 g / cm³. 3 .
[0046] Table 1. XRD diffraction peak information of cobalt carbonate obtained in step (2)
[0047]
[0048] Example 2:
[0049] A method for preparing cobalt tetroxide includes the following steps:
[0050] (1) Solution preparation: Prepare a cobalt sulfate metal solution with a cobalt ion concentration of 1.0 mol / L as a cobalt salt solution, and prepare an ammonium bicarbonate solution with a carbonate ion concentration of 2.0 mol / L as a precipitant solution.
[0051] (2) Cobalt carbonate synthesis: to 10m 3 Add 2m to the reactor 3 Sodium carbonate solution was used as the base liquid. The reaction temperature was 34℃, the stirring speed was 270 r / min, the cobalt salt solution flow rate was 500 L / h, and the precipitant solution flow rate was adjusted according to the pH value to control the reaction pH value at 7.6. After the slurry in the reactor was filled, the thickener was turned on for concentration. During the concentration, the cobalt salt solution and precipitant solution were continuously introduced to keep the material level in the reactor constant. After 41 h of reaction, the particle size D50 of the cobalt carbonate slurry was 6.8 μm. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was measured by XRD.
[0052] (3) Cobalt carbonate washing: The cobalt carbonate slurry was centrifuged to remove the mother liquor, and washed with pure water 3 times to obtain filter cake;
[0053] (4) Cobalt carbonate sintering: The cobalt carbonate filter cake obtained in step (3) is fed into a rotary kiln for high-temperature calcination. The kiln is equipped with a lifting plate, the height of which is 3% of the inner diameter of the furnace tube and the angle between the lifting plate and the tangent of the inner wall of the kiln is 50°. The rotary kiln feed frequency is 6Hz, the material layer height is 50% of the height of the lifting plate, and there are 12 heating temperature zones with temperature gradient settings. The calcination temperatures are 300-350-400-450-500-550-600-650-700-750-760-760, the calcination time for each section is 2h, the furnace tube speed is 18Hz, and the kiln inlet valve opening is 95%.
[0054] (5) Pneumatic conveying: The cobalt tetroxide sintered in the rotary kiln in step (4) is conveyed to the powder processing system through a positive pressure conveying system. The positive pressure conveying pressure is 0.13 MPa, the single conveying weight of the conveying pump is 95 kg, and the gas-solid ratio is 40 kg / kg. After pneumatic conveying, the material is mixed, sieved to remove iron, and packaged to obtain the finished cobalt tetroxide. The particle size D50 of the finished cobalt tetroxide is measured to be 4.62 μm, and the tap density TD is 2.67 g / cm³. 3 .
[0055] Example 3:
[0056] A method for preparing cobalt tetroxide includes the following steps:
[0057] (1) Solution preparation: Prepare a cobalt nitrate metal solution with a cobalt ion concentration of 1.5 mol / L as a cobalt salt solution, and prepare a sodium bicarbonate solution with a carbonate ion concentration of 2.5 mol / L as a precipitant solution.
[0058] (2) Cobalt carbonate synthesis: to 10m 3 Add 2m to the reactor 3 Sodium carbonate solution was used as the base liquid. The reaction temperature was 32℃, the stirring speed was 280 r / min, the cobalt salt solution flow rate was 500 L / h, and the precipitant solution flow rate was adjusted according to the pH value to control the reaction pH value at 7.7. After the slurry in the reactor was filled, the thickener was turned on for concentration. During the concentration, the cobalt salt solution and precipitant solution were continuously introduced to keep the material level in the reactor constant. After 50 h of reaction, the particle size D50 of the cobalt carbonate slurry was 7.95 μm. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was measured by XRD.
[0059] (3) Cobalt carbonate washing: The cobalt carbonate slurry was centrifuged to remove the mother liquor, and washed with pure water 3 times to obtain filter cake;
[0060] (4) Cobalt carbonate sintering: The cobalt carbonate filter cake obtained in step (3) is fed into a rotary kiln for high-temperature calcination. The kiln is equipped with a lifting plate, the height of which is 2% of the inner diameter of the furnace tube and the angle between the lifting plate and the tangent of the inner wall of the kiln is 50°. The rotary kiln feed frequency is 3Hz, the material layer height is 30% of the height of the lifting plate, and there are 12 heating temperature zones with temperature gradient settings. The calcination temperatures are 300-350-400-450-500-550-600-650-700-750-780-780, the calcination time for each section is 4h, the furnace tube speed is 13Hz, and the kiln inlet valve opening is 75%.
[0061] (5) Pneumatic conveying: The cobalt tetroxide sintered in the rotary kiln in step (4) is conveyed to the powder processing system through a positive pressure conveying system. The positive pressure conveying pressure is 0.10 MPa, the single conveying weight of the conveying pump is 80 kg, and the gas-solid ratio is 30 kg / kg. After pneumatic conveying, the material is mixed, sieved to remove iron, and packaged to obtain the finished cobalt tetroxide. The particle size D50 of the finished cobalt tetroxide is measured to be 6.76 μm, and the tap density TD is 2.76 g / cm³. 3 .
[0062] Comparative Example 1:
[0063] A method for preparing cobalt tetroxide includes the following steps:
[0064] (1) Solution preparation: Same as in Example 1;
[0065] (2) Cobalt carbonate synthesis: to 10m 3Add 2m to the reactor 3 Sodium carbonate solution was used as the base liquid. The reaction temperature was 40℃, the stirring speed was 80 r / min, the cobalt salt solution flow rate was 500 L / h, and the precipitant solution flow rate was adjusted according to the pH value to control the reaction pH value at 7.0. After the slurry in the reactor was filled, the thickener was turned on for concentration. During the concentration, the cobalt salt solution and precipitant solution were continuously introduced to keep the material level in the reactor constant. After 36 h of reaction, the particle size D50 of the cobalt carbonate slurry was 4.23 μm. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was measured by XRD. SEM image of cobalt carbonate as shown Figure 3 As shown, by Figure 3 It can be seen that the primary particles of cobalt carbonate are relatively large, exhibiting a "peak-shaped" morphology;
[0066] (3) Cobalt carbonate washing: Same as in Example 1;
[0067] (4) Cobalt carbonate sintering: Same as in Example 1;
[0068] (5) Pneumatic conveying: Same as in Example 1, SEM image of the finished cobalt tetroxide is shown below. Figure 4 As shown, the particle size D50 of the finished cobalt tetroxide was measured to be 3.75 μm, and the tap density TD was 2.23 g / cm³. 3 .
[0069] Comparative Example 2:
[0070] A method for preparing cobalt tetroxide includes the following steps:
[0071] (1) Solution preparation: Same as in Example 1;
[0072] (2) Cobalt carbonate synthesis: to 10m 3 Add 2m to the reactor 3 Sodium carbonate solution was used as the base liquid. The reaction temperature was 27℃, the stirring speed was 200 r / min, the cobalt salt solution flow rate was 500 L / h, and the precipitant solution flow rate was adjusted according to the pH value to control the reaction pH value at 8.0. After the slurry in the reactor was filled, the thickener was turned on for concentration. During the concentration, the cobalt salt solution and precipitant solution were continuously introduced to keep the material level in the reactor constant. After 36 h of reaction, the particle size D50 of the cobalt carbonate slurry was 4.23 μm. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was measured by XRD.
[0073] (3) Cobalt carbonate washing: Same as in Example 1;
[0074] (4) Cobalt carbonate sintering: Same as in Example 1;
[0075] (5) Pneumatic conveying: Same as in Example 1, SEM image of the finished cobalt tetroxide is shown below. Figure 5 As shown in the figure, particles are visible agglomerated and adhered together. The measured particle size of the finished cobalt tetroxide is D50 = 4.48 μm, and the tap density is TD = 2.31 g / cm³. 3 .
[0076] Comparative Example 3:
[0077] A method for preparing cobalt tetroxide includes the following steps:
[0078] (1) Solution preparation: Same as in Example 1;
[0079] (2) Cobalt carbonate synthesis: Same as in Example 1;
[0080] (3) Cobalt carbonate washing: Same as in Example 1;
[0081] (4) Cobalt carbonate sintering: The calcination temperatures are 300-400-500-600-700-700-700-700-700-700-700-700, the calcination time for each section is 2 hours, the kiln inlet valve opening is 65%, and the rest is the same as in Example 1.
[0082] (5) Pneumatic conveying: Same as in Example 1, the SEM image of the finished cobalt tetroxide is as follows. Figure 5 As shown, the particle size D50 of the finished cobalt tetroxide was measured to be 4.37 μm, and the tap density TD was 2.36 g / cm³. 3 .
[0083] Comparative Example 4:
[0084] A method for preparing cobalt tetroxide includes the following steps:
[0085] (1) Solution preparation: Same as in Example 1;
[0086] (2) Cobalt carbonate synthesis: Same as in Example 1;
[0087] (3) Cobalt carbonate washing: Same as in Example 1;
[0088] (4) Cobalt carbonate sintering: The height of the lifting plate inside the kiln is 0.1% of the diameter of the furnace tube, and the angle between the lifting plate and the tangent of the inner wall of the kiln is 40°. Other aspects are the same as in Example 1.
[0089] (5) Pneumatic conveying: Same as in Example 1, the particle size D50 of the finished cobalt tetroxide was measured to be 4.17 μm, and the tap density TD was 2.27 g / cm³. 3 .
[0090] Comparative Example 5:
[0091] A method for preparing cobalt tetroxide includes the following steps:
[0092] (1) Solution preparation: Same as in Example 1;
[0093] (2) Cobalt carbonate synthesis: Same as in Example 1;
[0094] (3) Cobalt carbonate washing: Same as in Example 1;
[0095] (4) Cobalt carbonate sintering: Same as in Example 1;
[0096] (5) Pneumatic conveying: The positive pressure conveying pressure is 0.05 MPa, the gas-solid ratio is 20 kg / kg, and other parameters are the same as in Example 1. The particle size D50 of the finished cobalt tetroxide was measured to be 4.06 μm, and the tap density TD was 2.47 g / cm³. 3 .
[0097] Comparative Example 6:
[0098] A method for preparing cobalt tetroxide includes the following steps:
[0099] (1) Solution preparation: Same as in Example 1;
[0100] (2) Cobalt carbonate synthesis: Same as in Example 1;
[0101] (3) Cobalt carbonate washing: Same as in Example 1;
[0102] (4) Cobalt carbonate sintering: Same as in Example 1;
[0103] (5) Pneumatic conveying: The positive pressure conveying pressure is 0.18 MPa, the gas-solid ratio is 60 kg / kg, and other parameters are the same as in Example 1. The SEM image of the finished cobalt tetroxide is shown below. Figure 6 As shown, the particle size D50 of the finished cobalt tetroxide was measured to be 3.59 μm, and the tap density TD was 2.38 g / cm³. 3 .
[0104] The test methods for the products provided in each embodiment and comparative example are as follows:
[0105] (1) Calculation method of grain size: The full width at half maximum (FWHM) of the diffraction peaks of the (104), (012) and (116) crystal planes in the X-ray diffraction pattern of cobalt carbonate is calculated using the Scherrer formula. The calculation formula is as follows: Where k is a constant, taken as 0.89; the values of half-width at half maximum (β) and diffraction angle (θ) are obtained by analyzing the XRD pattern. When using this formula to calculate the grain size, the half-width at half maximum (β) of the diffraction peak is converted to radians for calculation. A copper target is used as the X-ray source. Scanning speed 5° / min;
[0106] The average grain size is calculated using the formula: Average grain size = ((104) crystal plane grain size + (012) crystal plane grain size + (116) crystal plane grain size) / 3, with units of 1 / 3.
[0107] (2) Particle size D50: obtained using a Malvern 3000 laser particle size analyzer.
[0108] (3) Tap density TD: The test is performed using a tap density meter. The test method is based on the national standard GB / T21354-2008.
[0109] Comparing Example 1 and Comparative Example 1, it can be seen that the higher temperature, lower pH, and slower stirring speed during the preparation of cobalt carbonate increased the primary particle growth rate of cobalt carbonate. The average grain size of the top three strongest peaks (104), (012), and (116) of cobalt carbonate was larger. The SEM image also shows that the primary particles of cobalt carbonate obtained in Comparative Example 1 were relatively coarse, which reduced the surface energy and resulted in a lower tap density of the final cobalt tetroxide product.
[0110] Comparing Example 1 and Comparative Example 2, it can be seen that the temperature was lower and the pH was higher during the preparation of cobalt carbonate. The average grain size of the top three strongest peaks (104), (012), and (116) of the obtained cobalt carbonate was smaller, which resulted in a larger particle size D50 after sintering and pneumatic conveying. This indicates that agglomeration was still more serious, which also led to a lower tap density.
[0111] Comparing Example 1 with Comparative Examples 3 and 4, it can be seen that during the cobalt carbonate sintering process, changes in the kiln lifting plate structure and the widening of the sintering temperature zone intervals, as well as a reduction in the kiln air intake, can also lead to the agglomeration of cobalt tetroxide, resulting in a lower tap density.
[0112] Comparing Example 1 with Comparative Examples 5 and 6, it can be seen that after cobalt tetroxide sintering in the kiln is pneumatically conveyed, if the conveying pressure is too low and the gas-solid ratio is too low, the particles will not be fully opened up, resulting in the finished cobalt tetroxide particles being too large and the tapped density being too low. If the conveying pressure is too high and the gas-solid ratio is too high, the particles will be damaged, which will further reduce the tapped density.
Claims
1. A method for preparing cobalt tetroxide, characterized in that, Includes the following steps: (1) The cobalt salt solution is mixed with the precipitant solution containing carbonate to obtain cobalt carbonate slurry, wherein the average grain size of the top three strongest peaks of cobalt carbonate (104), (012), and (116) in the cobalt carbonate slurry is 160-180 Å. (2) After solid-liquid separation of the cobalt carbonate slurry, the solid phase is sintered and then depolymerized to obtain the final product; the pH of the mixing reaction is 7.5-7.8; the temperature of the mixing reaction is 30-35℃; the mixing reaction uses a precipitant solution as the base liquid, and cobalt salt solution and precipitant solution are added under stirring; the stirring speed is 200-300 r / min; the sintering method is multi-stage sintering with gradually increasing temperature, the initial sintering temperature of the multi-stage sintering is 250-350℃, the final sintering temperature of the multi-stage sintering is 750-800℃, and the temperature difference between two adjacent sintering stages of the multi-stage sintering is 0-5℃. At 0℃, the sintering time for each stage in the multi-stage sintering is 2-4 hours; the specific steps of the solid-phase sintering are as follows: the cobalt carbonate filter cake obtained by solid-liquid separation is put into a rotary kiln for high-temperature sintering. The kiln is equipped with a lifting plate, the height of which is 2%-5% of the inner diameter of the furnace tube, and the angle between the lifting plate and the tangent of the inner wall of the kiln is 50°-55°. The cobalt tetroxide sintered in the rotary kiln is transported to the powder processing system through a positive pressure conveying system. The positive pressure conveying pressure is 0.10-0.15 MPa, the gas-solid ratio is 30-50 kg / kg, and the material after pneumatic conveying is mixed, sieved to remove iron, and packaged to obtain the finished cobalt tetroxide.
2. The method for preparing cobalt tetroxide according to claim 1, characterized in that: The cobalt ion concentration in the cobalt salt solution is 1.0-2.0 mol / L.
3. The method for preparing cobalt tetroxide according to claim 1, characterized in that: The concentration of carbonate ions in the precipitant is 2.0-3.0 mol / L.
4. The method for preparing cobalt tetroxide according to claim 1, characterized in that: The particle size D50 of the cobalt carbonate slurry is 4-8 μm.
Citation Information
Patent Citations
Cobaltosic oxide, preparation method thereof, lithium cobalt oxide, positive pole piece and battery
CN119118214A
Cobalt carbonate and preparation method thereof, cobaltosic oxide and lithium ion battery
CN119461500A